Peningkatkan Keterampilan Mengomunikasikan Hasil Diskusi pada Materi Kegiatan Ekonomi Melalui Penerapan Model Pembelajaran Numbered Head Together (NHT) pada Peserta Didik Kelas IV Sekolah Dasar - D A Sari, Sukarno, Chumdari (Universitas Sebelas Maret, 2020)
Abstract. The purpose of this research is improving the skill of communicating the result of the discussion by applying numbered head together model. This Classroom Action Research consists of two cycles. The subjects of this research were 20-grade 4th elementary school students in Surakarta in the 2019/2020 academic year. The data collection techniques used interview, observation, and documentation. Data analysis techniques using triangulation. The analysis of the data used the interactive analysis model of Miles and Huberman that consists of data collection, data reduction, data display, and conclusion verifying. Research data shows that the score of the skills of communicating the result of the discussion on the pre-cycle is 20,8%, in the first cycle is 41,6%, and the second cycle is 87,5%. Based on the result of the research, it can be concluded that the skill of communicating the result of the discussion ongrade 4th elementary school students in the 2019/2020 academic year can be improved through the Numbered Head Together model.